Pengaruh Efisiensi Biaya Proyek terhadap Profitabilitas pada Perusahaan Konstruksi (Studi Kasus Periode 2021-2023) - Stefan, Yonatan Alvin (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
The construction industry in Indonesia plays an important role in driving national economic growth, but also faces major challenges in managing efficient project costs to maintain profitability levels. This study aims to examine the effect of project cost efficiency on the profitability of construction companies, using Return on Assets (ROA) as an indicator of financial performance. This study uses a quantitative approach with secondary data taken from the annual financial reports of construction companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. The analysis technique used is spearman correlation. The results of the study show that the Cost of Goods Sold to Revenue (COGS to Revenue) ratio has a significant negative effect on ROA, and Asset Turnover (ATO) also has a significant negative effect on ROA. Meanwhile, the Operating Expense Ratio variable shows a negative effect on ROA. These findings confirm that project cost efficiency and optimization of asset use play an important role in increasing the profitability of construction companies. The practical implication of this study is the need for a more effective cost and asset management strategy to maintain financial performance amidst the challenges of the construction industry.